2021
DOI: 10.21083/partnership.v16i1.6363
|View full text |Cite
|
Sign up to set email alerts
|

What is a Library Website, Anyway? Reconsidering Dominant Conceptual Models

Abstract: In late 2019, Thompson Rivers University embarked on a multi-phase website usability project beginning with a website user survey, to be followed shortly afterward by usability testing and interviews. While the survey was completed as planned, the COVID-19 pandemic closed the library and interrupted the usability testing phase. This interruption and the frantic website changes that followed led me to consider survey findings within the context of differing conceptual models of the library website as a whole. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Across the various studies, there were a number of consistent findings. Many authors found that websites could be improved by removing library jargon and simplifying the language (Gillis, 2017;Guay et al, 2019;Klein et al, 2018;Paterson, 2021;Tidal, 2012;Vargas Ochoa, 2020). Another commonality was that users benefitted when the site provided multiple access points to the same information, as multiple links all mapping to one page improved success rates (Valenti, 2019;Vargas Ochoa, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Across the various studies, there were a number of consistent findings. Many authors found that websites could be improved by removing library jargon and simplifying the language (Gillis, 2017;Guay et al, 2019;Klein et al, 2018;Paterson, 2021;Tidal, 2012;Vargas Ochoa, 2020). Another commonality was that users benefitted when the site provided multiple access points to the same information, as multiple links all mapping to one page improved success rates (Valenti, 2019;Vargas Ochoa, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%